2020
DOI: 10.1088/1757-899x/736/7/072004
|View full text |Cite
|
Sign up to set email alerts
|

Ozonolysis of wastewater from rubber industry

Abstract: The chemical industries currently release pollutants into air, soil, and water. For rubber industry, large amount of wastewater is produced resulting in huge energy demand for water treatment. However, there are several restriction factors for wastewater treatment i. e., contaminated oil from machinery and foul odour from organic matter caused by microbial enzymes. To overcome these problems, this research focused on wastewater treatment from rubber industry via ozonolysis. Two cases of experiments were carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…The addition of chemicals during the process, like ammonia (latex preservation) and sulfuric acid (skim latex coagulation), can cause the formation of various contaminants in the waste. Wastewater will harm the environmental ecosystem and human health if it is directly discharged [2]. It has been reported that the total dissolved solids (TDS) were 2240 mg/L, total suspended solids (TSS) were 3.512 mg/L, ammonia 94 mg/L, BOD 1340 mg/L and COD 2834 mg/L.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of chemicals during the process, like ammonia (latex preservation) and sulfuric acid (skim latex coagulation), can cause the formation of various contaminants in the waste. Wastewater will harm the environmental ecosystem and human health if it is directly discharged [2]. It has been reported that the total dissolved solids (TDS) were 2240 mg/L, total suspended solids (TSS) were 3.512 mg/L, ammonia 94 mg/L, BOD 1340 mg/L and COD 2834 mg/L.…”
mentioning
confidence: 99%
“…This value indicates that wastewater has high contamination and must be treated before being discharged into the environment [3].Rubber industrial wastewater treatment techniques have been carried out in several industries, but still, have limited and low efficiency. In general, the treatment of rubber industry wastewater in the Southeast region is based on biological processes, for example, lagoon systems, oxidation trenches, anaerobic digestion, and activated sludge [2]. However, this process requires a large area and still leaves an odour.…”
mentioning
confidence: 99%